Tetherless mobile micrograsping using a magnetic elastic composite material. (24th October 2016) - Zhang, Jiachen; Diller, Eric
Abstract: In this letter, we propose and characterize a new type of tetherless mobile microgripper for micrograsping that is made of a magnetic elastic composite material. Its magnetically-programmable material and structures make it the first three-dimensional (3D) mobile microgripper that is directly actuated and controlled by magnetic forces and torques. With a symmetric four-limb structure, the microgripper is 3.5 mm long from tip to tip when it is open and 30 μ m thick. It forms an approximate 700 μ m cube when it is closed. The orientation and 3D shape of the microgripper are determined by the direction and strength of the applied magnetic field, respectively. As a mobile device, the microgripper can be moved through aqueous environments for precise grasping and transportation of micro-objects, pulled by magnetic gradients directly or rolled in rotating magnetic fields. The deformation of the microgripper under magnetic actuation is characterized by modeling and confirmed experimentally. Being directly controlled by magnetic forces and torques, the microgripper is easier and more intuitive to control than other magnetic microgrippers that require other inputs such as thermal and chemical responses. In addition, the microgripper is capable of performing fast repeatable grasping motions, requiring no more than 25 ms to change from fully open to fully closed in water at room temperature. As a result of its large-amplitude 3D deformation, the microgripper can accommodate cargoes with a wide range of geometries and dimensions. A pick-and-place experiment demonstrates the efficacy of the microgripper and its potentials in biomedical, microfluidic, and microrobotic applications.